Role of DUOX in gut inflammation: lessons from Drosophila model of gut-microbiota interactions - Lee, Won-Jae; Kim, Sung-Hee (Frontiers in Cellular and Infection Microbiology, 2014)
It is well-known that certain bacterial species can colonize the gut epithelium and induce inflammation in the mucosa, whereas other species are either benign or beneficial to the host. Deregulation of the gut-microbe interactions may lead to a pathogenic condition in the host, such as chronic inflammation, tissue injuries, and even cancer. However, our current understanding of the molecular mechanisms that underlie gut-microbe homeostasis and pathogenesis remains limited. Recent studies have used Drosophila as a genetic model to provide novel insights into the causes and consequences of bacterial-induced colitis in the intestinal mucosa. The present review discusses the interactions that occur between gut-associated bacteria and host gut immunity, particularly the bacterial-induced intestinal dual oxidase (DUOX) system. Several lines of evidence showed that the bacterial-modulated DUOX system is involved in microbial clearance, intestinal epithelial cell renewal (ECR), redox-dependent modulation of signaling pathways, cross-linking of biomolecules, and discrimination between symbionts and pathogens. Further genetic studies on the Drosophila DUOX system and on gut-associated bacteria with a distinct ability to activate DUOX may provide critical information related to the homeostatic inflammation as well as etiology of chronic inflammatory diseases, which will enhance our understanding on the mucosal inflammatory diseases frequently observed in the microbe-contacting epithelia of humans.